'Turn‐on' fluorescent chemosensors based on naphthaldehyde‐2‐pyridinehydrazone compounds for the detection of zinc ion in water at neutral pH. (6th July 2017) - Liu, Yuanyuan; Li, Yuanyuan; Feng, Qi; Li, Na; Li, Kai; Hou, Hongwei; Zhang, Bing
Abstract: A series of naphthaldehyde‐2‐pyridinehydrazone derivatives were discovered to display interesting 'turn‐on' fluorescence response to Zn 2+ in 99% water/DMSO ( v / v ) at pH 7.0. Mechanism study indicated that different substituent groups in the naphthaldehyde moiety exhibited significant influence on the detection of Zn 2+ . The electron rich group resulted in longer fluorescence wavelengths but smaller fluorescence enhancement for Zn 2+ . Among these compounds, 1 showed the highest fluorescence enhancement of 19‐fold with the lowest detection limit of 0.17 μmol/L toward Zn 2+ . The corresponding linear range was at least from 0.6 to 6.0 μmol/L. Significantly, 1 showed an excellent selectivity toward Zn 2+ over other metal ions including Cd 2+ .